Syariah Principles in Culinary Marketing: A Dialectical Study of Profitability and Business Morality - Arif Budiman; Wargo; Nurjali; Erwina Kartika Devi (Journal of Economics and Social Sciences (JESS), 2026)
The culinary industry in the modern era is characterized by hyper-competition, often leading business practitioners to prioritize short-term profitability over ethical considerations, which results in deceptive marketing practices. This study aims to analyze the dialectical relationship between profitability and business morality by examining the marketing strategies of the Pagi Sore eatery in Talang Babat from the perspective of Islamic business ethics. Employing a descriptive-qualitative case study approach, data were gathered through in-depth interviews, passive participant observation, and documentation studies, subsequently analyzed using an interactive model of data reduction and inductive reasoning. The results demonstrate that the eatery successfully internalizes prophetic values shiddiq (truthfulness), amanah (trustworthiness), fathanah (wisdom), and tabligh (advocacy) into its marketing mix, particularly through halalan thoyyiban product assurance and transparent pricing. Crucially, the findings reveal a "Location Paradox," where the consistent application of Sharia principles serves as a potent moderating variable that neutralizes geographical disadvantages and fosters organic consumer loyalty through integrity-based competitive advantage. This study concludes that Islamic business ethics is not merely a normative religious obligation but a sophisticated strategic asset that ensures long-term business resilience and profitability. By transforming locational challenges into market strengths, this research provides a replicable framework for small-scale enterprises to harmonize ethical integrity with commercial success in a saturated market.